Antineoplastic Drug-Induced Cardiotoxicity: A Redox Perspective - Varricchi, Gilda; Ameri, Pietro; Cadeddu, Christian; Ghigo, Alessandra; Madonna, Rosalinda; Marone, Giancarlo; Mercurio, Valentina; Monte, Ines; Novo, Giuseppina; Parrella, Paolo; Pirozzi, Flora; Pecoraro, Antonio; et al. (Frontiers in Physiology, 2018)
Antineoplastic drugs can be associated with several side effects, including cardiovascular tox-icity (CTX). Biochemical studies have identified multiple mechanisms of CTX. Chemoterapeutic agents can alter redox homeostasis by increasing the production of reactive oxygen species (ROS) and reactive nitrogen species RNS. Cellular sources of ROS/RNS are cardiomyocytes, endothelial cells, stromal and inflammatory cells in the heart. Mitochondria, peroxisomes and other subcellular components are central hubs that control redox homeosta-sis. Mitochondria are central targets for antineoplastic drug-induced CTX. Understanding the mechanisms of CTX is fundamental for effective cardioprotection, without compromising the efficacy of anticancer treatments. Type 1 CTX is associated with irreversible cardiac cell in-jury and is typically caused by anthracyclines and conventional chemotherapeutic agents. Type 2 CTX, associated with reversible myocardial dysfunction, is generally caused by biologicals and targeted drugs. Although oxidative/nitrosative reactions play a central role in CTX caused by different antineoplastic drugs, additional mechanisms involving directly and indirectly cardiomyocytes and inflammatory cells play a role in cardiovascular toxicities. Identification of cardiologic risk factors and an integrated approach using molecular, imaging, and clinical data may allow the selection of patients at risk of developing chemotherapy-related CTX. Although the last decade has witnessed intense research related to the molecular and biochemical mechanisms of CTX of antineoplastic drugs, experimental and clinical stud-ies are urgently needed to balance safety and efficacy of novel cancer therapies.